A new species of nurse-frog (Aromobatidae, Allobates) from the Madeira River basin with a small geographic range - Simões, Pedro Ivo (Zootaxa, 2016)
I describe the seventh species of nurse-frog (Allobates) from the Madeira River basin in Brazilian Amazonia. The new species is distinguished from similar congeneric species by its small body size (snout-to-vent length ranging between 14.0–14.7 mm in adult males and between 14.7–14.9 mm in adult females), by the absence of dark brown regular shapes (e.g. hourglass, “X” or polygon-like marks) on the dorsum, by the absence of transverse dark bars on the dorsal surface of the thigh, and by the light gray to white ventral surfaces, light to dark gray only on throat in live male and female specimens. Males have a distinctive advertisement call characterized by the emission of long (7–11 s) trills of short notes (0.04 s in average) with dominant frequency at 5.9–6.3 kHz and emission rate ranging between 6.7–8.7 notes/s. DNA barcode analyses based on a fragment of the 16S rDNA mitochondrial gene provides additional support to the recognition of the new taxon, which is probably distributed on the east riverbank of the Madeira River, in the interfluve between the Aripuanã and Ji-Paraná rivers.